Phylogeny, biogeography, and morphological evolution among and within the Neotropical and Asian clades of Schefflera (Araliaceae). Issue 6 (20th February 2020) - Plunkett, Gregory M.; Lowry, Porter P.; Fiaschi, Pedro; Frodin, David G.; Nicolas, Antoine N.
Abstract: Schefflera is the largest and most complex genus of Araliaceae, with ~600 described species (and many additional species awaiting formal description), but recent studies indicate that it is polyphyletic, forming five geographically centered clades spread across the major lineages of the family. Significant progress has been made in revising the three smallest clades, but the two largest groups, centered in Asia and the Neotropics, remain poorly understood. To advance our knowledge of these groups, a taxon set of 211 Schefflera samples and 38 samples representing other genera of Araliaceae (including all genera of the "Asian Palmate clade") was assembled, from which sequences were obtained for six DNA spacer regions, including two nuclear (ITS, ETS) and four plastid markers ( rpl32‐trnL, trnF‐rpl32, trnK‐rpl16, psbA‐trnH ). Results were compared to an informal system of classification based on morphology. They confirm the monophyly of both the Asian and Neotropical groups, and their inclusion within the Asian Palmate clade, but not as sister groups. In the Neotropical clade, five major subclades can be recognized, four corresponding closely to morphological groupings (Cephalopanax, Crepinella, Didymopanax, Sciodaphyllum) and one that is geographically coherent (Gleasonia). Within Asian Schefflera, there are four major subclades, corresponding closely to currently recognized informal groups (Agalma, Heptaphyllum, Heptapleurum, Hypoleucoi). Biogeographic analyses suggest that both the Asian and Neotropical groups can trace their origins to SE Asia, where Asian Schefflera is still well represented and where Chengiopanax, the possible sister group of Neotropical Schefflera, is native. Trait‐evolution analyses of a remarkable series of convergences in habit, foliar, and reproductive characters suggest multiple independent origins (and some reversals), both within and between the Neotropical and Asian clades of Schefflera .